Mediating effects of workgroup processes on the relationship between nurse turnover and nurse outcomes in hospitals - Bae, Sung-Heui; Kim, Suin; Myung, Hwasook (Frontiers in Public Health, 2023)
Background Nurse turnover is often considered to be an outcome, and few studies have investigated its consequences in nursing care. The underlying mechanism of the nurse turnover–nurse outcome relationship has not been empirically investigated. Therefore, this study examines workgroup processes and nurse outcomes as the consequences of nurse turnover and the mediating effect of workgroup processes on the nurse turnover–nurse outcomes relationship. Methods A cross-sectional design was adopted to investigate the data collected from 264 staff nurses. Furthermore, six-month turnover rates, workgroup processes (nurse–nurse collaboration, team cohesion), and nurse outcomes (job satisfaction, intent to leave) were utilized in the multivariate regression models. Results Overall, 53 (24.4%) nurses had worked in nursing units with a zero six-month turnover rate. The average mean six-month turnover rate was 15.5%. Nurse turnover adversely affected nurses’ job satisfaction and several subscales of team cohesion including task cohesion and social cohesion. Team cohesion partially mediated the relationship between nurse turnover and job satisfaction. Conclusion Nurse turnover decreased job satisfaction and team cohesion, and team cohesion partially mediated the nurse turnover–nurse outcomes relationship. These findings provide evidence supporting the significant adverse effects of nurse turnover and suggest the potential role of workgroup processes in explaining the underlying mechanism of the relationship between nurse turnover and nurse outcomes. Implications for nursing and health policy Healthcare organizations must create a positive work environment to reduce nurse turnover. Further, states and countries should try to develop and establish nursing and health policies to prevent turnover.